Analisis Komunikasi Efektif Terhadap Peningkatan Kinerja Karyawan pada PT. Kencana Mulia Abadi Sibolga - Heriyawan Hutagalung; Mansur Tanjung; Fauziah Nur Simamora (Universitas Pahlawan Tuanku Tambusai, 2022)
performance can be done by implementing effective communication. This study aims to analyze effective communication on improving employee performance at PT. Kencana Mulia Abadi Sibolga. The sample in this study were all employees of PT. Kencana Mulia Abadi Sibolga which opened 31 people. The analytical method used for testing and proving the hypothesis is a descriptive quantitative approach. The results showed that there was a positive relationship between effective communication and employee performance at PT. Kencana Mulia Abadi Sibolga is 0.757, so if it is interpreted on a scale it can be categorized as sufficient. The regression equation obtained is Y= 12,491+0,637 X which shows the effect of effective communication on employee performance. The t test shows that the proposed hypothesis is accepted as true, where t count 6.241 > t table 2.0452, which means that employee performance will increase the regression coefficient/slop (0.573) if the effective communication variable is added by one unit. Based on the research results obtained between effective communication and improving employee performance at PT. Kencana Mulia Abadi Sibolga has a positive relationship, it can be seen from the increase in the number of consumers in the last 5 years as many as 310 people. Keyword: Effective, Employee, Performance, Communication, Improvement